Pengolahan Air Sungai Menggunakan Slow Sand Filter Sistem Downflow dalam Menurunkan COD dan BOD - Hamidah, Laily Noer; Urifatus Eka Kurnia Sari; Lily Oktavia (Journal of Research and Technology, 2022)
The raw water used as drinking water is currently contaminated with industrial, domestic, and agricultural waste, resulting in high concentrations of nitrogen, phosphate, detergent, COD and pesticides. Slow sand filters can be used as an effort to treat drinking water. This study aims to determine the effect of the variables used on the reactor performance for the removal of COD and BOD nutrients. In this study, the variation of gravel (with and without gravel) is used, so that the performance of each type of reactor can be seen. While the parameters to be measured are COD and BOD. The results showed that SSF gave a good reduction performance in reducing BOD up to 60% and COD up to 68.33% on the 6th day.